A remarkable new fossil Malthodes (Coleoptera, Cantharidae, Malthininae) from Baltic amber - Pankowski, Madeline V. (Zootaxa, 2025)
A remarkable new soldier beetle, Malthodes (s. str.) susanbuttsae sp. nov., is described and illustrated from Eocene Baltic amber. This fossil species exhibits exceptional preservation of the terminal abdominal segments, which are highly variable at the species level among males of this genus. Also provided is a brief discussion examining the various factors that may have shaped the modifications of the terminal urites of Malthodes males.